INNOVATION OF PALM SUGAR DIGITAL MARKETING THROUGH LEGAL POLICY IN VILLAGE DEVELOPMENT SERVICES - Yunus, Yudin; Arman; Ali, Almer Hassan; Mandey , Lucia Cecilia; Lefina, Silvya; Koapaha, Teltje (LP2M Universitas Bina Mandiri Gorontalo, 2024)
Digital Marketing Innovation of Palm Sugar Through Legal Policy in Village Development Service is the implementation of Kosabongan's community service. With the implementing team and assistants interested in further exploring this hot theme and providing technology and innovation results to the community, especially implementing partners where the Granule packaging machine produces palm sugar packaging from traditional to modern. The ant palm sugar mixer machine produces small modern rectangular palm sugar. Its marketing is a traditional word-of-mouth marketing system with direct sales and promotions at local events. With the presence of Kosabongan, a digital intelligent marketing system is created for predicting palm sugar sales. The method in implementing this service is with stages: socialization, training, application of technology, assistance and evaluation, and ensuring sustainability. Successfully increasing sales and skills of craftsmen, expanding market access, and supporting the village economy. Regulatory support and ongoing assistance are very important for the sustainability of the program and can be a model for other villages. Shows the importance of technology adaptation and regulatory support in developing local products. This success emphasizes that digital marketing is not just about selling products but also empowering craftsmen to be more independent and competitive. Legal support and ongoing assistance ensure that craftsmen comply with regulations, protect their products, and maximize market potential. This model is important to be adopted in other villages because it not only improves the local economy but also provides a strong foundation for sustainable growth by integrating technology and policies in village development.